The Interpersonal Costs and Rewards of Confronting Sexism - Akhtar, Muna. (2018)
Abstract: The present studies sought to examine the contexts that increase women's willingness to confront instances of sexism. In particular, I sought to understand how a bystander's reaction to a confrontation may affect the confronter's feelings of isolation and intention to confront sexism in the future. Results show that when bystanders reward women for confronting sexism, confronters report feeling less isolated than when bystanders discourage confronters or stay silent. Furthermore, a bystander's silence may feel as discouraging as an explicitly negative response (e.g., "you're a troublemaker") to confronters because confronters are in a vulnerable position and are seeking social support. Confronters who are met with silence from bystanders may feel as isolated as those who are met with a negative response, and, thus, feel just as alone. Though previous literature has emphasized the need to decrease interpersonal costs, these results suggest that this may not be enough for confronters of sexism.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Psychology.; Advisor: Jessica Remedios.; Committee: Robyn Mallett, and Keith Maddox.; Keywords: Social psychology, Experimental psychology, and Psychology.